PENGARUH KOMPENSASI, KOMUNIKASI, DAN BEBAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PT. PUSAKA - Edi Siregar; Vidya Nourma Linda (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2022)
This study aims to determine the effect of Compensation, Communication, and Workload on Job Satisfaction of Employees of PT. Pusaka Graha Teknik. Determination of the sample in this study amounted to 54 samples using the census research method through the distribution of questionnaires. The analysis used is multiple linear analysis with this research is a research with causality with quantitative techniques. The data processing program used is the SPSS (Statistical Package for the Social Sciences) version 21 program. The results obtained that simultaneously Compensation, Communication, and Workload have a positive and significant effect on job satisfaction, and partially Compensation has a positive and significant effect on job satisfaction while communication and workload have no positive and significant effect on job satisfaction.